Barriers and facilitators to accessing and utilising sexual and reproductive health services during the COVID-19 pandemic in Africa: a systematic review and meta-analysis - Obasanjo Afolabi Bolarinwa; Clifford Odimegwu; Kobi V. Ajayi; Tosin Olajide Oni; Rajeeb Kumar Sah; Akanni Akinyemi (BMC Health Services Research)
Abstract Background Ensuring uninterrupted access and utilisation of sexual and reproductive health (SRH) services remains crucial for preventing adverse SRH outcomes. However, the unprecedented emergence of the 2019 coronavirus disease (COVID-19) significantly disrupted most of these services in Africa. Thus, we systematically reviewed and examined barriers and facilitators to accessing and utilising SRH services during the COVID-19 pandemic in Africa. Methods We systematically searched five databases for relevant articles published between January 2020 to December 2022, and the articles were screened following the JBI and PRISMA guidelines. Meta-synthesis of barriers and facilitators to accessing and utilising SRH services during the COVID-19 pandemic were reported, while a meta-analysis of the pooled prevalence of barriers to accessing and utilising SRH services during the COVID-19 pandemic in Africa was analysed using R. Results The pooled prevalence of barriers to accessing and utilising SRH services during the COVID-19 pandemic in Africa was 26%. Seven themes were developed for the identified barriers (disruption of healthcare services, fear and misinformation, limited availability of resources, place & region of residence, healthcare staff attitude/manpower, limited access to transportation, and stigma and discrimination), whilst six themes were developed for the identified facilitators (support for vulnerable populations, socio-demographic characteristics, community outreach programs, policy adaptations, telemedicine and digital health, and change in choice of sexual and reproductive commodities). Conclusion This study found that the COVID-19 pandemic significantly impacted SRH service access and utilisation in Africa. We recommend that future research consider a longitudinal examination of the pandemic on African SRH services. Trial registration PROSPERO registration number: CRD42022373335.